2017
DOI: 10.1007/s40268-017-0200-1
|View full text |Cite
|
Sign up to set email alerts
|

Methodological Study of Vancomycin Dosing in Elderly Patients Using Actual Serum Creatinine Versus Rounded Serum Creatinine

Abstract: PurposeThe practice of intentional rounding up of serum creatinine (SCr) in elderly patients with low measured values can lead to an underestimation of creatinine clearance and subsequent inaccurate dosing of medications. Thus, the purpose of this study was to evaluate the accuracy of vancomycin dose calculations for patients aged ≥65 years using an SCr rounded up to 1 mg/dL versus actual SCr.MethodsThis study compared the difference between measured steady-state vancomycin trough concentrations with predicted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…The study results suggest that actual serum creatinine levels may more accurately predict vancomycin troughs than rounded serum creatinine values. (22) The results of this study produced similar results to our own, suggesting older patients with rounded low serum creatinine values did not achieve vancomycin trough levels as readily as patients with higher serum creatinine levels, nor is the up-rounded serum creatinine value indicative of true renal function. Bourguignon and colleagues evaluated the pharmacokinetics of patients over the age of 80 years on vancomycin and found that there can be large inter-individual variability of vancomycin pharmacokinetic parameters.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The study results suggest that actual serum creatinine levels may more accurately predict vancomycin troughs than rounded serum creatinine values. (22) The results of this study produced similar results to our own, suggesting older patients with rounded low serum creatinine values did not achieve vancomycin trough levels as readily as patients with higher serum creatinine levels, nor is the up-rounded serum creatinine value indicative of true renal function. Bourguignon and colleagues evaluated the pharmacokinetics of patients over the age of 80 years on vancomycin and found that there can be large inter-individual variability of vancomycin pharmacokinetic parameters.…”
Section: Discussionsupporting
confidence: 83%
“…However, a discussion of appropriate vancomycin dosing in elderly patients was recently started with Young and colleagues. (22) Based on the data described above, limited national dosing guidelines, and the common practice of rounding serum creatinine to 1 mg/dl in elderly patients with serum creatinine levels of <1 mg/dl, more clinical data is needed to better understand the vancomycin utilization in the elderly population. The aim of this study was to evaluate vancomycin target trough attainment and the time to target trough attainment with vancomycin dosing per pharmacy in elderly patients, specifically in patients 75 years of age or older.…”
Section: Introductionmentioning
confidence: 99%
“…According to the results of a current systematic review [ 30 ], using urinary CrCL is the best diagnostic method for estimating drug dosing in augmented renal clearance (ARC). 24-hour urine collection is often difficult, and some limitations are reducing the accuracy of collecting urine within 24 hours [ 31 , 32 ]. In case of the critical condition of the ICU, requiring quick decision-making urine collection can be implemented by decreasing the time of urine collection.…”
Section: Discussionmentioning
confidence: 99%
“…By rounding SCr up to 0.8 mg/dL, we may have potentially underestimated CrCl and therefore inappropriately dose reduced certain drugs. Considering newer publications on this topic, we are in the process of updating our protocol by removing the rounding component 10,23‐25 . Patients for this study were identified from a report capturing the progress note template used for the protocol.…”
Section: Discussionmentioning
confidence: 99%